Learning software user interface design model for children with cerebral palsy - Nuraini Hidayah Sulaiman 1989-, author 602524; Masitah Ghazali, supervisor 555308; Fakulti Komputeran 538688 (Skudai : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2015